â€œBASINTOJIKâ€ BERSUMBER DARI KESENIAN â€œCALEMPONG RARAK GODANGâ€ DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Azrizer Azrizer; Asep Saepul Haris; Arnailis Arnailis (Institut Seni Indonesia Padangpanjang, 2024)
The composition